Effect of bolt relaxation on surface micro dynamic fatigue and wear. (October 2019) - Jiao, Xueyan; Cai, Ligang; Liu, Zhifeng; Yang, Congbin; Zhao, Yongsheng; Cheng, Qiang
Abstract: Because of the friction and damping effect between the interfaces, when the bolted structure bears the axial load, there will be no interface dislocation and only axial reciprocating tension and pressure, so it is difficult to have fretting fatigue and wear. Only under the tangential load, the interface will be staggered and the peaks and valleys between the micro-convex bodies will be alternately rubbed. After repeated cycles, the interface will generate sliding and adhesion areas of micro-fatigue and wear. Therefore, this paper conducts an in-depth study on the influence of bolt relaxation on surface fretting fatigue and wear. The relationship between tightening torque and clamping force, design and implementation of tangential relaxation experiment and acquisition and analysis of 3d surface topography are studied.